Applied systems analysis : engineering planning and technology management - de Neufville, Richard; De Neufville, Richard (New York : McGraw Hill Education, 1990)
The object of this book is to help the student and practitioner learn to apply systems analysis sucessfully and productively. It is addressed to the user, who has to know how to select the techniques appropriate in any situation, to apply them to real problems, and to interpret their results intelligently.
Part I: System optimization -- Part II: System evaluation
Includes index.
Keywords: ENGINEERING ECONOMY